2016
DOI: 10.1016/j.meteno.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Acidithiobacillus ferrooxidans's comprehensive model driven analysis of the electron transfer metabolism and synthetic strain design for biomining applications

Abstract: Acidithiobacillus ferrooxidans is a gram-negative chemolithoautotrophic γ-proteobacterium. It typically grows at an external pH of 2 using the oxidation of ferrous ions by oxygen, producing ferric ions and water, while fixing carbon dioxide from the environment. A. ferrooxidans is of great interest for biomining and environmental applications, as it can process mineral ores and alleviate the negative environmental consequences derived from the mining processes. In this study, the first genome-scale metabolic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 54 publications
0
21
0
2
Order By: Relevance
“…With the exception of At. ferrooxidans ATCC23270, for which a genomescale reconstruction was built (Campodonico et al, 2016), bioleaching bacterial metabolic reconstructions corresponded to reduced and simplified representations of their networks in all cases. This was also the case for A. thiooxidans Licanantay, for which we previously built a small stoichiometric model used to predict its growth rate in different media containing different reduced sulfur compounds for oxidation (Bobadilla Fazzini et al, 2013).…”
Section: A Thiooxidans Licanantay Metabolic Networkmentioning
confidence: 99%
“…With the exception of At. ferrooxidans ATCC23270, for which a genomescale reconstruction was built (Campodonico et al, 2016), bioleaching bacterial metabolic reconstructions corresponded to reduced and simplified representations of their networks in all cases. This was also the case for A. thiooxidans Licanantay, for which we previously built a small stoichiometric model used to predict its growth rate in different media containing different reduced sulfur compounds for oxidation (Bobadilla Fazzini et al, 2013).…”
Section: A Thiooxidans Licanantay Metabolic Networkmentioning
confidence: 99%
“…ferrooxidans [13,15,16], A. thiooxidans [23] and A. caldus [20]. A recent model-driven study of genes in A. ferrooxidans suggested that an increase in extracellular polymer substances (EPS) could be achieved by introducing several genetic knock downs [54].…”
Section: Plasmids Of Incq Incp and Incw Groups Have Been Shown To Fumentioning
confidence: 99%
“…EPS is important in bioleaching applications as it facilitates bacterial adhesion to the sulfide minerals [54]. Other gene disruption studies and subsequent responses to various metal ions have been reported for Metallosphaera sedula and development of a more characterized genetic system is underway [55].…”
Section: Plasmids Of Incq Incp and Incw Groups Have Been Shown To Fumentioning
confidence: 99%
“…Na extração por biolixiviação, o minério é grosseiramente fracionado, disposto em pilhas de 6 a 8 metros de altura sobre uma superfície impermeável e constantemente irrigadocom uma solução ácida (pH< 2,0) contendo o inóculo bacteriano [8,9]. Esta solução é constantemente recirculada através da pilha, sendo enriquecida em íons Fe 3+ e H + derivados do processo de oxidação do sulfeto metálico pelas bactérias oxidantes de ferro e enxofre, resultando na oxidação do Cu + em Cu 2+ , solúvel em água [9]. Posteriormente, o cobre metálico lixiviado é recuperado através de métodos eletroquímicos e a solução reciclada pela adição de nutrientes, voltando a ser irrigada no topo da pilha.…”
Section: Introductionunclassified